Skema Distribusi dalam Islam - Saparuddin Saparuddin (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2015)
In economic literature, the term distribution has two connotations, namely; first; distribution associated with the production or the continuation of production activities. Second; distribution associated with income distribution. distribution are various strategies that do (marketing strategy) so that the product can be up to the hands of consumers by the number, the place and the right time. Distribution of the meaning of the spread of prosperity is essential in the teaching of Islam, as revealed by Allah in the Qur'an. al-Hashr / 59: 7, namely that wealth (assets) not circulate among the rich only. This verse contains the teaching that poor people become the responsibility of affluent people to sympathize and give social security. Party sufficiency and sympathize this in the Islamic view assumed by the state.